Blender 3D basics beginner's guide : a quick and easy-to-use guide to create 3D modeling and animation using Blender 2.7 /: a quick and easy-to-use guide to create 3D modeling and animation using Blender 2.7. ([2014]) - Fisher, Gordon
No abstract available